1985
DOI: 10.1557/proc-58-389
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Rapidly Solidified Nickel-Base Superalloys and Intermetallics

Abstract: The improvements in the mechanical properties of nickel-base alloys that have been made possible by rapid solidification processing are reviewed.The results of processing by powder metallurgy, laser melting, low pressure plasma deposition and spray forming are examined.In general, the increased homogeneity obtained by rapid solidification allows for increased alloying and improved hot workability.The refined grain size improves the low and intermediate temperature strength, but leads to lower strengths at high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The key benefit was the ability to produce a rapidly solidified form in the deposited state without a subsequent need for thermomechanical processing. 31 In a recent study at the State University of New York at Stony Brook, the authors and coworkers examined two compositions of intermetallics: an L1 zbased Ni3A1 alloy (in wt. %: Ni-6.4Cr-10.8AI-IHf-O.05B-0.05C) and two-phase NiAI-Ni3AI (Ni-20 wt.% Al).3Z For both alloys, which were approximately 3 mm thick, nearly theoretically dense test specimens were obtained by VPS processing.…”
Section: Intermetallicsmentioning
confidence: 99%
“…The key benefit was the ability to produce a rapidly solidified form in the deposited state without a subsequent need for thermomechanical processing. 31 In a recent study at the State University of New York at Stony Brook, the authors and coworkers examined two compositions of intermetallics: an L1 zbased Ni3A1 alloy (in wt. %: Ni-6.4Cr-10.8AI-IHf-O.05B-0.05C) and two-phase NiAI-Ni3AI (Ni-20 wt.% Al).3Z For both alloys, which were approximately 3 mm thick, nearly theoretically dense test specimens were obtained by VPS processing.…”
Section: Intermetallicsmentioning
confidence: 99%
“…Jones [3] and Boettinger [4] were also able to use the rapid solidification method to cause grain size [3] and micro segregation [4] refinement in various alloys. These refinements have also been said to improve physical properties of alloys: increases in yield and ultimate strength being reported by Jones [3], Taub and Jackson reported that rapid solidification could also lead to increased toughness [5], while Kang et al, reported an increase in resistance to corrosion [6].…”
mentioning
confidence: 99%